The Insurance Value of CSR during the Financial Crisis in Taiwan (International Journal of Management and Sustainability, 2021)
This study examines the impact of CSR activities on corporate financial performance by using data from 514 listed companies in Taiwan during the period of the 2008 financial crisis. To measure the CSR performance, this study refers to independent international CSR valuation institutions to compile CSR indicators for individual Taiwanese firms. The results show that CSR activities before the 2008 financial crisis are associated with positive stock returns during the crisis. In addition, after comparing the in-crisis and post-crisis periods, it is found that CSR indeed offers an insurance value for a firm’s stock performance during the crisis period. We conclude that CSR does play a protective role for firms when a market encounters a widespread trust crisis. Furthermore, the results highlight the importance of wider engagement in CSR practices for firms, not only to boost their reputation but also for the insurance value, which will pay off during unexpected negative trust events.